Strategi UMKM bertahan melewati Covid-19: menjadi fleksibel dan kolaboratif - Nopriadi Saputra; Evi Satispi; Danang Prihandoko (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
COVID-19 does not only cause a physical and mental health crisis, but also an economic crisis. Micro, Small and Medium Enterprises (MSMEs) as pillars of the national economy need business resilience to survive. This article tries to discuss the ability of MSMEs for resilience, flexibility, and collaboration. This article is an attempt for answering the question whether business flexibility and collaboration capability have a positive and significant impact on MSME resilience. A cross-sectional quantitative study was conducted to answer this question. The study involved 506 owners and/or managers of MSMEs in Java and Sumatra as respondents. The data obtained were analyzed using SmartPLS version 3. From the results of statistical analysis, it was concluded that MSME resilience was influenced by business flexibility and collaboration capabilities of MSMEs. Collaboration capability has a direct or indirect effect on business resilience, but business flexibility does not play a mediator role. To increase business resilience, MSMEs can develop business flexibility based on digital technology and collaboration.